THE IMPACT OF GREENWASHING IN THE COSMETIC INDUSTRY, PARTICULARLY FOCUSING ON A REAL-WORLD CASE (INNISFREE’S GREEN FOREST CAMPAIGN) - Handoyo, Louis Priscilla Ribka; Umayati, Dwi Khusnul (Sanata Dharma University, 2025)
Innisfree's Green Forest campaign promotes ecological awareness, but its sustainability claims are contradicted by the use of plastic in its packaging. Therefore, this study aims to expose the greenwashing practices employed by Innisfree. This study examines the impact of Innisfree’s greenwashing on its brand image. This case study used an ecolinguistics framework by Fill Mühlhäusler (2001) to reveal how Innisfree’s environmental narratives were constructed and what strategies they used to attract their customers back. As per the Method section, the data were Instagram comments and their sales performance data. The analysis was conducted in 4 steps: (1) examining Innisfree’s Instagram posts that had been targeted by netizen criticism, (2) categorizing netizens’ comments into deception, loss of trust, and demand for transparency, (3) evaluating the alignment between Innisfree’s environmental messaging and consumer responses, and (4) assessing the impact of greenwashing on sales. This study highlights that the environmentally friendly language used in advertisements—often disguised as campaigns—serves a specific purpose within the ecolinguistics conception, which is to persuade people to follow the advertisement's intended message. The findings indicate that greenwashing negatively impacted Innisfree’s brand image, however, the use of influencers successfully mitigated the damage caused by the scandal.